Working Mother Issue: The Effect of Family Emotional Support on Work-Family Conflict: Working Mother Issue: The Effect of Family Emotional Support on Work-Family Conflict - Sekar Afrila Miftakhul Jannah; Anissa Lestari Kadiyono; Diana Harding (Journal of Family Sciences, 2022)
The increase in gender equality, women finally have the same opportunities as men in various aspects, including employment. Therefore, the demands experienced by working mothers are increasing, both from work and family. The difficulty of meeting all these demands can lead to work-family conflict, and one factor that can reduce work-family conflict is family emotional support. This study aimed to determine the effect of family emotional support on work-family conflict in mothers who worked as civil servants in the Indonesian Army Education Training and Doctrine Command. Using a non-experimental quantitative design with simple random sampling, this study was conducted in 2021 with 68 female participants who were married and had children. Participants were requested to fill out a questionnaire for 5-10 minutes. Using regression analysis, the result showed no significant effect of family emotional support on work-family conflict in mothers who worked as civil servants in the Indonesian Army Education Training and Doctrine Command. Thus, it can be concluded that participants most likely need other forms of support, such as instrumental support and other sources of support, such as support provided in the workplace or a combination of various forms and sources of social support.